Advances in neuroimaging to improve care in sickle cell disease. Issue 5 (May 2021) - Jordan, Lori C; DeBaun, Michael R; Donahue, Manus J
Summary: Sickle cell disease is associated with progressive and increased neurological morbidity throughout the lifespan. In people with sickle cell anaemia (the most common and severe type of sickle cell disease), silent cerebral infarcts are found in more than a third of adolescents by age 18 years and roughly half of young adults by age 30 years, many of whom have cognitive impairment despite having few or no conventional stroke risk factors. Common anatomical neuroimaging in individuals with sickle disease can assess structural brain injury, such as stroke and silent cerebral infarcts; however, emerging advanced neuroimaging methods can provide novel insights into the pathophysiology of sickle cell disease, including insights into the cerebral haemodynamic and metabolic contributors of neurological injury. Advanced neuroimaging methods, particularly methods that report on aberrant cerebral blood flow and oxygen delivery, have potential for triaging patients for appropriate disease-modifying or curative therapies before they have irreversible neurological injury, and for confirming the benefit of new therapies on brain health in clinical trials.